2010
DOI: 10.1159/000316803
|View full text |Cite
|
Sign up to set email alerts
|

Trajectory Analysis of Serum Biomarker Concentrations Facilitates Outcome Prediction after Pediatric Traumatic and Hypoxemic Brain Injury

Abstract: Traumatic brain injury (TBI) and hypoxic ischemic encephalopathy (HIE) are leading causes of morbidity and mortality in children. Several studies over the past several years have evaluated the use of serum biomarkers to predict outcome after pediatric brain injury. These studies have all used simple point estimates such as initial and peak biomarker concentrations to predict outcome. However, this approach does not recognize patterns of change over time. Trajectory analysis is a type of analysis which can capt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
33
5

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(40 citation statements)
references
References 85 publications
2
33
5
Order By: Relevance
“…S100B showed similar dynamics as in previous studies with the highest concentrations within 48 hours of admittance to the NICU 25 . Previous studies of S100B in the context of sTBI, have also observed a secondary peak, where the secondary peaks were correlated to secondary injury, however, in the current study, we did not observe any obvious secondary peaks [26][27][28] . It is worth mentioning that the delta value for the secondary peak observed in the previous studies was very small compared with the S100B levels found at day 1.…”
Section: Discussioncontrasting
confidence: 91%
“…S100B showed similar dynamics as in previous studies with the highest concentrations within 48 hours of admittance to the NICU 25 . Previous studies of S100B in the context of sTBI, have also observed a secondary peak, where the secondary peaks were correlated to secondary injury, however, in the current study, we did not observe any obvious secondary peaks [26][27][28] . It is worth mentioning that the delta value for the secondary peak observed in the previous studies was very small compared with the S100B levels found at day 1.…”
Section: Discussioncontrasting
confidence: 91%
“…S100B cannot penetrate the blood-brain barrier in the normal condition; however, when neuroglial cells undergo necrosis, S100B is leaked and penetrates across the injured blood-brain barrier, increasing its level in serum (Chen et al, 2008). The serum S100B level reflects the degree of damage, and is useful in the evaluation of the therapeutic efficiency of drugs and of the prognosis of the central nervous system (Fishler et al, 1965;Egberts et al, 2008;Murabayashi et al, 2008;Berger et al, 2010;Gyorgy et al, 2011). In this study, the results showed that the S100B level of preterm infants with cerebral white damage 1 day after birth had no significant difference with that of normal preterm infants, and that S100B concentration increased on the 3rd day and peaked on the 7th day; however, with the improvement of body condition, there was an obvious decrease on the 14th day.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, serum MBP could reflect brain injury severity, therapeutic efficiency, and prognosis (Egberts et al, 2008;Murabayashi et al, 2008;Gyorgy et al, 2011;Zhou et al, 2013). Berger et al (2010) reported that the detection of S100B and MBP serum concentrations is important for predicting prognosis, and that MBP had an accuracy of 73% and specificity of 61%, and S100B had a sensitivity of 59% and specificity of 100%. Gyorgy et al (2011) also demonstrated that higher S100B and MBP serum levels indicated poorer prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…80 Although associations between increased levels of biomarkers and poorer outcomes may be statistically significant, the specificity and sensitivity of isolated measurements are low. More sophisticated analyses of temporal profiles of biomarkers, 81 multiple profiles of biomarkers 82 and biomarker profiles in combination with clinical data 83 have been proposed. Neurophysiological biomarkers of brain function soon after injury that predict outcome have also been developed, although most of them are research tools and are not in widespread clinical use.…”
Section: What Investigations May Help Predict Outcome?mentioning
confidence: 99%